Telaah Nilai-Nilai Pendidikan Karakter dalam Buku Sejarah Kebudayaan Islam Kelas VI Kurikulum 2013 Terbitan Yudhistira - Nazhiifah Zalfaa; Dewi Utami; Alfi Satria (Lembaga Pengembangan Kinerja Dosen, 2024)
The 2013 Curriculum in Indonesia emphasizes character education as a core part of student development. The values of character education in this curriculum are often referred to as the 18 Character Values. The curriculum aims to foster well-rounded students and also possess strong ethical values. This study examines the values of character education in the book of Islamic Cultural History for sixth grade, published by Yudhistira. The study analyzes character education values in the book and its alignment with the Curriculum 2013. The study is a library research. To interpret and analyze the issues of character education values in the book which is reflected the Curriculum 13, the study uses content analysis. The findings indicate that the character education values presented in the book are aligned with the Curriculum 2013. The values found in the study includes 18 characters which are grouped into five main pillars religiousness, nationalism, independence, cooperation and integrity. The values are being religious, honest, tolerance, discipline, hard working, creative, independent, democratic, curious, nationalist, communicative, responsible, peace-loving, aware of environment and social, love for the homeland, appreciate for the achievements, and love for reading.